Effect of using some organic fertilizers and marine algae extract on the growth and production of cucumber in plastic green house - ibraheem, nour (Latakia University Journal -Biological Sciences Series, 2025)
The research was carried out in the village of Hmeimim, affiliated to the Jableh region in Lattakia Governorate, in an unheated plastic hall, during the agricultural season 2023 to study the effect of some organic fertilizers and marine algae extract on the vegetative and floral growth of cucumbers. The experiment was conducted on the hybrid cucumber "Romano F1", which is a female hybrid that produces only female flowers. Two types of organic fertilizer were used in the study: fish pond sediment fertilizer and organic fertilizer (composed of sheep, poultry and cow waste) and marine algae extract. The study included 4 treatments: T0 control plants, T1 plants with fish pond sediment added at a rate of 300 g/m2, T2 plants with fermented and dried organic fertilizer added at a rate of 500 g/m2, T3 plants sprayed with marine algae extract at a concentration of 1.50 ml/l and 4 replicates for each treatment and 10 plants in each replicate, so the number of plants in the experiment becomes 160 plants according to the complete randomized block design. Readings were taken related to the vegetative indicators of cucumber plant as well as the indicators of flowering and fruiting (for early-growing fruits). The results showed: The addition of fish pond sediments increased plant height (305.20 cm) and the number of branches formed on the plant (18.09 branches) and outperformed the control treatment and the highest number of female flowers (56.97 flowers/plant) and the number of fruits (45.61 fruits/plant) and with significant differences with the rest of the treatments. The foliar spray treatment with marine algae extract outperformed in the number of leaves (56.39 leaves/plant), leaf surface area (19609cm2), and leaf surface index (8.17) over all treatments; While the treatment of fish pond sediments achieved the highest production per plant of 5.27 kg/plant and the highest productivity per unit area of ​​21.92 kg/m2, outperforming the rest of the treatments. Therefore, fish pond sediments and marine algae extract can be used on cucumber plant "Romano F1"to improve and increase vegetative and floral growth indicators.